A DESCRIPTIVE STUDY ON TEACHER-STUDENT INTERACTION IN SPEAKING CLASS AT THE EIGHTH YEAR OF SMP NEGERI 1 GEMOLONG IN 2010/2011 ACADEMIC YEAR - WULANDARI, DIDID FITRI (2011)
The subject of this descriptive research is the eighth year of SMP Negeri 1 Gemolong in 2010/2011 academic year. The objectives of this research are: (1) to identify the teacher-students interaction in the speaking class at the eighth year of SMP N 1 Gemolong, and (2) to identify the problems occur in speaking class at the eighth year of SMP N 1 Gemolong. The writer uses descriptive qualitative research. The writer gets the data of this research from event, informant, and document. The events in this research are all of the activities occurred in the speaking class. Informants are the English teacher and the students of eighth year of SMP Negeri 1 Gemolong. Documents are all of the written information related to the interaction in speaking class. The method of collecting data is observation, interview, and data analysis of interaction in speaking class. After analyzing data, the researcher finds that (1) the teacher-students interaction in speaking class is good. Both of the teacher and the students play a part in every step of teaching learning process actively. The teacher implemented three steps of teaching cycle, namely Opening, Core Learning, and Closing that can be elaborated into BKOF, MOT, JCOT, and ICOT. The language uses in speaking class are teacher's modifying language, teacher's question, feedback, learners' language use in the classroom. Based on the Brown's interaction analysis system, there are five categories of the teacher-students' interaction happened in speaking class. (2) the problems faced by the students are students get difficulty in vocabulary, grammar mastery and pronunciation. Meanwhile the problems faced by the teacher are the students' indolence and the students are less open-minded, and the other problem was in looking for the idea.